Analisis Zat Warna Merah Sintetik pada Selai Stroberi yang Dijual di Pasar Tradisional Kota Depok - Ayuningtyas, Putri; Sauriasari, Rani; Kurniadi, Maryati (UI Scholars Hub, 2012)
Jam is a semi-solid food products made of fruit cooked with sugar that used as aflavoring on bakery including strawberry jam. Strawberry jam is added to food additives such as food dyes. The purpose of this study is to know about ponceau 4R, allura red, rodamin B, and amaran in the sample of strawberry jam in the traditional market at Depok City and to determine the levels of synthetic red dyes that are permitted on the sample strawberry jam. The method applied was dye isolation with wool and followed by analysis using a color reaction, then followed by paper chromatography using mobile phase n-butanol-eth-anol-water (3:4:4) and isobutanol-ethanol-water (3:2:4 ) and also TLC Densitometri using eluent ethanol-n-butanol-water (3:7:1). The result of study that from eight that has been investigated, it was found that six of them was contained ponceau 4R with levels of each sample at 0, 01164; 0, 00469; 0, 00974; 0, 00283; 0, 00482 and 0, 00435% still safe to consume.